WICK SYSTEM IN VARIOUS NUTRITION COMBINATIONS ON PAKCOY GROWTH AND YIELD - Agustina, Rohmatin; Oktaviani, Widya; Jumadi, Rahmad; Ardiansyah, Heri (Jurnal Agrotek Tropika, 2025)
This study aimed to examine the growth and yield of cabbage (Brassica rapa L.) plants grown in a hydroponic wick system using varying doses of AB Mix nutrients and Azolla liquid organic fertilizer (POC). POC Azolla is expected to serve as a replacement nutrient in hydroponics. In this study, a one-factorial group randomized design was used where P0: no POC Azolla nutrient and P1: AB Mix 100%; P2: POC Azolla 100%; P3: AB Mix 90% + POC Azolla 10%; P4: AB Mix 75% + POC Azolla 25%; P5: AB Mix 60% + POC Azolla 40%; P6: AB Mix 45% + POC Azolla 55%; P7: AB Blend 30% + POC Azolla 70%; P8 : AB Mix 15% + POC Azolla 85%. Three replicates of each treatment were performed. Annova was used for data analysis: Duncan's distance test should be performed at a significant level of 5% if a difference is found. The average growth variables of plant height (16.5 cm), number of leaves (18 strands), root length (18.33 cm), fresh plant weight (81.17 g) and dry plant weight (4.42 g) showed the same trend in the combination (AB Mix 75% + POC Azzola 25%), suggesting that this combination could be an alternative to the AB Mix 100% treatment.  The hydroponic cultivation of the wick system on Pakcoy plants has not been able to prove the use of POC Azzola alone. The use of POC Azzola is at least able to reduce the use of AB Mix by 25%.